Analisis Sistem Kelistrikan pada Beban Motor Mesin Pencacah Sampah Plastik - Yanolanda Suzantry Handayani; Junas Haidi; Agun Mardian (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2021)
In this modern era, the activities of almost all humans depend on machines they make, such as single-phase induction electric motors, which are used to chop plastic waste. This chopping machine aims to help plastic collectors process plastic waste into small pieces, making it easier to pack and ship plastic out of the area for reprocessing. The plastic waste shredding machine is made using a crushing system with a fan-shaped blade construction consisting of 39 blades divided by two rotating rows opposite the cover box using a chain motor gear transmission element. Most of the chopper machines on the market use engines with diesel or diesel fuel, therefore a chopper machine using an electric motor is designed to compare the motor power without the addition of capacitors and capacitors. The waste load used for motors without additional capacitors, medium and large bottles measuring 375 ml to 1500 ml, the machine can chop as much as 800 grams with the highest measurement of power 578.0 Watt, current 4.192 A, the lowest motor speed measurement is 1414 rpm and the reducer speed is 22.9 rpm . The waste load used for motors with additional capacitors, medium and large bottles measuring 375 ml to 1500 ml, the machine can chop 1000 grams with the highest measurement of power 732.7 Watt, current 4.149 A, the lowest motor speed measurement is 1464 rpm and the reducer speed is 22.9 rpm.